Globalization Goes Local: Nationalism in Indonesian Jazz - Wishnoebroto Wishnoebroto (Lingua Cultura, 2010)
Article presented how Jazz, as a product of American popular culture, can be very local in Indonesia. Nationalism, in this case, refers to how Indonesian jazz artists translate and create a kind of ‘dialogue’ between jazz and local Indonesian culture. The study used library research by finding what values that jazz had in order to create such dialogue, and how Indonesian nationalism could be transformed in jazz. The evolution of Jazz in Indonesia and the attitude of Indonesian jazz audience were discussed to see the position of jazz in Indonesian popular culture mainstream. It can be concluded that Jazz seems to deconstruct the common notion that music should be understood to be enjoyed. In jazz,  the irrational and sometimes absurd combination between jazz and other indigenous culture, has created a specific kinds of the music itself. Jazz in Indonesia has gone through its own cycle of evolution where the western and the eastern culture has created its own art and nobody knows the direction of jazz in the future.